Malnutrition during late pregnancy exacerbates high-fat-diet-induced metabolic dysfunction associated with lower sympathetic nerve tonus in adult rat offspring. (2nd June 2020) - Venci, Renan de Oliveira; Ramos, Gabriel Bortoli; Martins, Isabela Peixoto; Matiusso, Camila Cristina Ianoni; Saavedra, Lucas Paulo Jacinto; Ribeiro, Tatiane Aparecida; Pavanello, Audrei; Prates, Kelly Valério; Tófolo, Laize Peron; Moraes, Ana Maria Praxedes de; Fabricio, Gabriel Sergio; de Oliveira, Júlio Cezar; et al.
Abstract : Objectives: We aimed to assess the effects of a maternal protein-caloric restriction diet during late pregnancy on the metabolism of rat offspring fed a high-fat diet (HFD) during adulthood. Methods: During late pregnancy, rat dams received either a low-protein (4%; LP group) or normoprotein (23%; NP group) diet. After weaning, the offspring were fed a standard diet (Control; C). Male offspring (60 days old) from both groups were then fed either the C diet or HFD until they were 90 days old. The adult offspring and maternal metabolic parameters and autonomic nervous system (ANS) were then evaluated. Results: Dams exhibited low body weight gain and food intake during the LP diet consumption. At lactation, these dams showed high body weight gain, hypoinsulinemia and hyperglycemia. The maternal LP diet resulted in low body weights for the pups. There were also no differences in the metabolic parameters between the adult LP offspring that were fed the C diet and the NP group. Adults of both groups that were fed the HFD developed obesity associated with altered insulin/ glucose homeostasis and altered ANS activity; however, the magnitudes of these parameters were higher in the LP group than in the NP group. Conclusions: Maternal protein malnutrition during the last third of pregnancy malprograms the metabolism of rat offspring, resulting in increased vulnerability to HFD-induced obesity, and the correlated metabolic impairment might be associated with lower sympathetic nerve activity in adulthood.